1993
DOI: 10.2135/cropsci1993.0011183x003300010012x
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Reciprocal Recurrent Selection in BSSS and BSCB1 Maize Populations

Abstract: Improvement of germplasm as a parental source for developing inbreds has been an important part of most maize (Zea mays L.) breeding programs. Reciprocal recurrent selection is a cyclical breeding procedure designed to improve the interpopulation cross of two base populations. The objective of this study was to evaluate the direct and indirect responses of 11 cycles of reciprocal recurrent selection in the BSSS(R) (Iowa Stiff Stalk Synthetic) and BSCB1(R) (Iowa Corn Borer Synthethic no. 1) maize populations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
3
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 0 publications
9
107
3
8
Order By: Relevance
“…Keeratinijakal and Lamkey (1993a) reported that 11 cycles of RRS increased grain yield of the interpopulation cross (BSSS(R)Cn×BSCB1(R)Cn) by an average of 7% per cycle. Inbreeding depression for the interpopulation cross, as measured by selfing their F 1 , also increased with cycles of selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeratinijakal and Lamkey (1993a) reported that 11 cycles of RRS increased grain yield of the interpopulation cross (BSSS(R)Cn×BSCB1(R)Cn) by an average of 7% per cycle. Inbreeding depression for the interpopulation cross, as measured by selfing their F 1 , also increased with cycles of selection.…”
Section: Discussionmentioning
confidence: 99%
“…Increased grain yield has been the primary target of selection, with reduced grain moisture at harvest and increased resistance to root and stalk lodging (lodging is when a plant falls towards a horizontal position) as secondarily selected traits. Selection has been highly successful; mean grain yield of the interpopulation cross improved 77% by cycle 11, relative to cycle 0, with concurrent favorable responses in the other traits (Keeratinijakal and Lamkey 1993a).…”
Section: Sampling Of Populations and Rflp Analysismentioning
confidence: 99%
“…Em programas com populações temperadas (BS10 e BS11) submetidas à SRR de irmãos germanos por oito ciclos, Eyherabide & Hallauer (1991) reportaram ganho de 6,5% por ciclo. Keeratinijakal & Lamkey (1993), ao trabalhar com as populações BSSS e BSBC1 por 11 ciclos, relataram ganho de 6,95% com a seleção por ciclo. Santos et al (2007) obtiveram resposta média de 7,2% à seleção após três ciclos com as populações de milho tropical EPB4 e EPB5.…”
Section: Methodsunclassified
“…Idealizado por Comstock et al (1949), como um processo de melhoramento de duas populações e do híbrido entre elas, a seleção recorrente recíproca (SRR) com famílias de meios-irmãos paternos interpopulacionais e a recombinação de progênies S 1 têm proporcionado, na maioria dos casos, resultados favoráveis -com milho e milho-pipoca -, em relação à produção, resistência a pragas e doenças, resistência ao acamamento, entre outros caracteres (Keeratinijakal & Lamkey, 1993;Rademacher et al, 1999;Butron et al, 2000). A mesma afirmação pode ser feita em relação às modificações do método realizadas por Paterniani (1967), que sugeriu o uso de famílias de meios-irmãos maternos interpopulacionais e recombinação de progênies de meios-irmãos; e por Lonnquist & Williams (1967) e Hallauer & Eberhart (1970), que propuseram o emprego de progênies de irmãos-completos interpopulacionais e recombinação de famílias S 1 , para o melhoramento das populações e do híbrido, e de famílias de irmãos-completos interpopulacionais endogâmicas, para a obtenção de híbridos de linhagens.…”
Section: Introductionunclassified